An Orthotopic Patient-Derived Xenograft (PDX) Model Allows the Analysis of Metastasis-Associated Features in Colorectal Cancer - De Angelis, Maria Laura; Francescangeli, Federica; Nicolazzo, Chiara; Xhelili, Eljona; La Torre, Filippo; Colace, Lidia; Bruselles, Alessandro; Macchia, Daniele; Vitale, Sara; Gazzaniga, Paola; Baiocchi, Marta; Zeuner, Ann (Frontiers in Oncology, 2022)
Metastasis is the primary cause of death in patients with colorectal cancer (CRC), urging the need for preclinical models that recapitulate the metastatic process at the individual patient level. We used an orthotopic patient-derived xenograft (PDX) obtained through the direct implantation of freshly dissociated CRC cells in the colon of immunecompromised mice to model the metastatic process. Ortho-PDX engraftment was associated to a specific set of molecular features of the parental tumor, such as epithelial-to-mesenchymal transition (EMT), TGF pathway activation, increased expression of stemness-associated factors and higher numbers of circulating tumor cells (CTCs) clusters expressing the metastatic marker CD44v6. A parallel analysis of orthotopic/metastatic xenografts and organoids showed that tumor cells underwent mesenchymal-to-epithelial transition at the metastatic site and that metastasis-derived organoids had increased chemotherapy resistance. These observations support the usefulness of ortho-PDX as a preclinical model to study metastasis-related features and provide preliminary evidence that EMT/stemness properties of primary colorectal tumors may be crucial for orthotopic tumor engraftment.